2019
DOI: 10.1002/ecy.2848
|View full text |Cite
|
Sign up to set email alerts
|

Seedling recruitment correlates with seed input across seed sizes: implications for coexistence

Abstract: Understanding controls on recruitment is critical to predicting community assembly, diversity, and coexistence. Theory posits that at mean fecundity, recruitment of highly fecund small-seeded plants should be primarily microsite limited, which is indicated by a saturating recruitment function. In contrast, species that produce fewer large seeds are more likely to be seed-limited, which is characterized by a linear recruitment function. If these patterns hold in nature, seed predation that disproportionately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We previously reported initial results from a seed addition experiment in grasslands in western Montana where we found that the recruitment of species possessing functional traits including large‐seededness, taller height, lower C/N ratio and lower water use efficiency were less negatively affected by bunchgrass competition than smaller‐seeded species that were less tall, had higher C/N ratios and higher water use efficiency (Maron, Hajek, Hahn, & Pearson, 2018). However, within the context of the same experiment, we also demonstrated that post‐dispersal seed predation by mice had greater suppressive effects on the recruitment of larger‐seeded species compared to smaller seeded ones, thereby working in the opposite direction of bunchgrass competition (Maron et al, 2018; Maron, Hajek, Hahn, & Pearson, 2019). In temperate grasslands, old fields and other habitats, a growing body of work indicates that rodents focus on larger‐seeded species, disproportionately suppressing their recruitment compared to smaller‐seeded species (Dylewski, Ortega, Bogdziewicz, & Pearson, 2020; Brown & Heske, 1990; Larios, Pearson, & Maron, 2017; Maron, Pearson, Potter, & Ortega, 2012; Reader, 1993).…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…We previously reported initial results from a seed addition experiment in grasslands in western Montana where we found that the recruitment of species possessing functional traits including large‐seededness, taller height, lower C/N ratio and lower water use efficiency were less negatively affected by bunchgrass competition than smaller‐seeded species that were less tall, had higher C/N ratios and higher water use efficiency (Maron, Hajek, Hahn, & Pearson, 2018). However, within the context of the same experiment, we also demonstrated that post‐dispersal seed predation by mice had greater suppressive effects on the recruitment of larger‐seeded species compared to smaller seeded ones, thereby working in the opposite direction of bunchgrass competition (Maron et al, 2018; Maron, Hajek, Hahn, & Pearson, 2019). In temperate grasslands, old fields and other habitats, a growing body of work indicates that rodents focus on larger‐seeded species, disproportionately suppressing their recruitment compared to smaller‐seeded species (Dylewski, Ortega, Bogdziewicz, & Pearson, 2020; Brown & Heske, 1990; Larios, Pearson, & Maron, 2017; Maron, Pearson, Potter, & Ortega, 2012; Reader, 1993).…”
Section: Introductionmentioning
confidence: 54%
“…Fourth, are spatial differences in the performance of individual species across a productivity gradient manifest at the community level by shifting CWMs for traits? Finally, one important initial result of our prior work was that regardless of whether we manipulated interactions or not, species with higher annual fecundity (and hence that had more seeds initially added to plots) experienced greater recruitment than species with lower annual fecundity (Maron et al, 2018, 2019). Thus, does bunchgrass competition or seed predation equalize or exaggerate initial differences in relative abundances of target species that are related to fecundity?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, research on plant community assembly has focused on evaluating how the abiotic environment acts a ‘filter’ selecting for those species and traits that are best suited for particular environments. Although much work has evaluated trait–abiotic environment relationships (Cornwell & Ackerly, 2010; Kraft et al., 2011; Spasojevic & Suding, 2012), fewer studies have examined how herbivores may mediate these effects (Eskelinen et al., 2012; Maron et al., 2019). The little work that has been performed has focused on large grazers.…”
Section: Introductionmentioning
confidence: 99%